Socio-economic inequality and meningococcal disease - Stuart, James M.; Middleton, Nicos; Gunnell, David J. (My University, 2002)
Incidence of meningococcal disease was associated with socioeconomic deprivation across a rural English region. In young children the incidence was twice as high in the most deprived compared with the least deprived electoral wards. By addressing social inequalities the incidence of this serious infection could be reduced.
Keywords: Ecology; Meningococcal disease; Social deprivation